Innovations in Doctoral Training and Research on Tinnitus: The European School on Interdisciplinary Tinnitus Research (ESIT) Perspective - Schlee, Winfried; Hall, Deborah A.; Canlon, Barbara; Cima, Rilana F. F.; de Kleine, Emile; Hauck, Franz; Huber, Alex; Gallus, Silvano; Kleinjung, Tobias; Kypraios, Theodore; Langguth, Berthold; Lopez-Escamez, José A.; et al. (Frontiers in Aging Neuroscience, 2018)
Tinnitus is a common medical condition which interfaces many different disciplines, yet it is not a priority for any individual discipline. A change in its scientific understanding and clinical management requires a shift towards multidisciplinary cooperation, not only in research but also in training. The European School for Interdisciplinary Tinnitus research (ESIT) brings together a unique multidisciplinary consortium of clinical practitioners, academic researchers, commercial partners, patient organizations and public health experts to conduct innovative research and train the next generation of tinnitus researchers. ESIT supports fundamental science and clinical research projects in order to: 1) advancing new treatment solutions for tinnitus, 2) improving existing treatment paradigms, 3) developing innovative research methods, 4) performing genetic studies on 5) collecting epidemiological data to create new knowledge about prevalence and risk factors, 6) establishing a pan-European data resource. All research projects involve inter-sectoral partnerships through practical training, quite unlike anything that can be offered by any single university alone. Likewise, the postgraduate training curriculum fosters a deep knowledge about tinnitus whilst nurturing transferable competencies in personal qualities and approaches needed to be an effective researcher, knowledge of the standards, requirements and professionalism to do research, and skills to work with others and to ensure the wider impact of research. ESIT is the seed for future generations of creative, entrepreneurial, and innovative researchers, trained to master the upcoming challenges in the tinnitus field, to implement sustained changes in prevention and clinical management of tinnitus, and to shape doctoral education in tinnitus for the future.